Motivating the use of real-time multimodal travel planners: the role of users value, technophile and community resilience - Dastjerdi, Aliasghar Mehdizadeh; Kaplan, Sigal; e Silva, Joao de Abreu; Nielsen, Otto Anker; Pereir, Francisco Camara (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
Advanced traveler Information systems (ATIS) have the potential to improve travel experience, enhance personal mobility and productivity, since they allow travelers to make better informed travel decisions. However, understanding the motivators underlying individuals’ intentions to use the system is essential to evaluate the effectiveness of this solution for promoting sustainable travel trends. The aim of this paper is to find the drivers that influence decisions in using such systems on an individual level. Perceived values developed by using the new system, technophile and community resilience constructs are incorporated in the framework in order to better explain user-sided heterogeneity observed in individual behavior. The case-study focuses on a new ATIS in Copenhagen. It questions 822 Danish citizens by distributing a technology-use preference survey. Structural equation models revealed that the drivers are specific to individual users and depends on wide ranging factors that go above traditional economic and socio-demographic methods. The results show a) different value dimensions perceived by individuals for the new information system and different effects on its adoption b) a relation between different community resilience constructs and value dimensions c) a stronger appeal of using the system to individuals who are technophile and value the usefulness of the new information system to increase trip efficiency.